Pengembangan Perangkat Pembelajaran Berbasis Problem Based Learning Materi Persamaan dan Pertidaksamaan Linear Satu Variabel Kelas VII SMP/MTs - Isnaini, Nur; Yuanita, Putri; Kartini (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
Mismatches between teacher-created learning tools and 2013 curriculum requirements affect students’ level of understanding of learning materials, primarily linear equations and inequalities of one variable. This study aims to create a learning tool based on problem-based learning of linear equation materials and one-variable inequalities that is valid and practical for class VII SMP/MTs. The resulting learning tools are a syllabus, a learning implementation plan (RPP), and a student activity sheet (LAS). This learning tool is a development study using a 4D model that consists of four stages: definition, design, development, and dissemination. The means of this research were verification sheets and student response questionnaires. The data analysis performed is a validity analysis and a utility analysis. The syllabus, lesson, and LAS validation results show very valid criteria with average validation values ​​of 3.64, 3.60, and 3.61, respectively. The results of limited LAS testing showed that LAS met very practical criteria with an average utility value of 3.61. A problem-based learning tool for linear equations and inequalities in one variable class VII SMP / MT meets valid and practical criteria based on validation and limited test results. It can be used in the learning process.